Islamic Educational Systems and Institutions During the Prophet Muhammad SAW - Zainuddin Zainuddin (Jurnal Pendidikan Islam Indonesia, 2023)
The first Islamic education was carried out by the Prophet Muhammad SAW, a prophet and teacher who succeeded in creating a superior generation as the output of Islamic education. His ability to foster and form a community that has a high civilization is the best education system of all time. As a form of effort to grow and make human beings as stated in the word of Allah SWT and in the National Education System Law No. 20 of 2003 is through Islamic Education. The results showed that the Islamic education system during the time of Prophet Muhammad SAW consisted of 4 components, namely 1) the goals of Islamic education were developing all human potential (tarbiyah), transferring knowledge from teacher to student (ta'lim), and educating morals and character (ta'dib), 2) educator tasks that must be fulfilled (make a clear work plan for the progress of students, make oneself a model or role model), and characteristics that must be possessed (sincere, honest, practicing knowledge, fair, noble character, tawadhu', courageous, cheerful, patient, guarding speech, consulting), 3) educational institutions (home, mosque, as-suffah, al-Khuttab), 4) methods (discussion and giving feedback, telling stories, parables and case studies, pictures and graphics) and the techniques applied (i.e. conditioning the learning atmosphere, interacting actively through auditory and visual interactions, using body language, doing self-reflection, giving affirmations and repetition, teaching the core of the lesson, guessing with questions, familiarizing students with various challenges, being honest , observe and classify.